Analysis and Design of a Maglev Permanent Magnet Synchronous Linear Motor to Reduce Additional Torque in dq Current Control - Feng Xing; Baoquan Kou; Lu Zhang; Tiecheng Wang; Chaoning Zhang (Energies, 2018)
The maglev linear motor has three degrees of motion freedom, which are respectively realized by the thrust force in the x-axis, the levitation force in the z-axis and the torque around the y-axis. Both the thrust force and levitation force can be seen as the sum of the forces on the three windings. The resultant thrust force and resultant levitation force are independently controlled by d-axis current and q-axis current respectively. Thus, the commonly used dq transformation control strategy is suitable for realizing the control of the resultant force, either thrust force and levitation force. However, the forces on the three windings also generate additional torque because they do not pass the mover mass center. To realize the maglev system high-precision control, a maglev linear motor with a new structure is proposed in this paper to decrease this torque. First, the electromagnetic model of the motor can be deduced through the Lorenz force formula. Second, the analytic method and finite element method are used to explore the reason of this additional torque and what factors affect its change trend. Furthermore, a maglev linear motor with a new structure is proposed, with two sets of 90 degrees shifted winding designed on the mover. Under such a structure, the mover position dependent periodic part of the additional torque can be offset. Finally, the theoretical analysis is validated by the simulation result that the additionally generated rotating torque can be offset with little fluctuation in the proposed new-structure maglev linear motor. Moreover, the control system is built in MATLAB/Simulink, which shows that it has small thrust ripple and high-precision performance.